SITUASI KEBAHASAAN PADA MASYARAKAT JAWA DI DESA TEMAWANG BULAI KECAMATAN SEPAUK KABUPATEN SINTANG - Rizky Oktiyadi; Nanang Heryana; Agus Syahrani (Universitas Tanjungpura, 2019)
AbstractThis study aims to describe the linguistic situation in Javanese people in Temawang Bulai Village, Sepauk Subdistrict, Sintang District which covers three aspects of discussion, namely language skills, language selection, and language attitude. This research is based on a sociolinguistic approach by applying quantitative research methods. However, to validate and strengthen the research data, triangulation techiniques are used in qualitative research. As a data source, researchers used 22 samples (respondents) of research. The results of this study indicate that the linguistic situation in the Javanese community in Temawang Bulai Village, Sepauk Subdistrict, Sintang district is in an unsafe status, because of the indicated language shift. The results of this study also show that there has been a decline in the ability of Javanese, which includes lexical recognition, translation task, and discourse test. Then, the results of this study also show that the pattern of language selection in Javanese people in Temawang Bulai Village,Sepauk Subdistrict, Sintang District, overall show the pattern of language selection which tends to be the same, namely using more Dayak Seberuanglanguage. However, the results of this study indicate that Javanese in Temawang Bulai Village,Sepauk Subdistrict, Sintang District, have a positive attitude towards Javanese. Keywords: Language Situation, Language Ability, Language Selection, Language Attitude, Domain